2015
DOI: 10.1186/s13673-015-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

INSPECT: extending plane-casting for 6-DOF control

Abstract: INSPECT is a novel interaction technique for 3D object manipulation using a rotation-only tracked touch panel. Motivated by the applicability of the technique on smartphones, we explore this design space by introducing a way to map the available degrees of freedom and discuss the design decisions that were made. We subjected INSPECT to a formal user study against a baseline wand interaction technique using a Polhemus tracker. Results show that INSPECT is 12% faster in a 3D translation task while at the same ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…But using a also been conside rtphone become settings the sma nteraction whil ed cultural herit e smartphone to martphone move nd [19,23] …”
Section: Chara Discrimin Tangiblementioning
confidence: 99%
“…But using a also been conside rtphone become settings the sma nteraction whil ed cultural herit e smartphone to martphone move nd [19,23] …”
Section: Chara Discrimin Tangiblementioning
confidence: 99%
“…Several researchers have proposed to use handheld touchscreens in spatial user interfaces for tasks such as sketching, ideation and modeling (e.g., [3,23,25,33,48,91]), navigation of volumetric data [106], 3D data exploration [65] and system control [10]. Spatial manipulation has mostly been studied in single-user settings (e.g., [5,51,63,68,74,111,112]) but also in collaborative settings [35].…”
Section: Spatial Interactionmentioning
confidence: 99%
“…With the Inertial Measurement Unit (IMU), phone-orientation (3DoF) has been used to point at distant screens [11,15,44,50] and in VR [16,32] via ray-casting. The IMU has furthermore been used for the selection and manipulation of objects in 3D environments via 2D rotational planes [19,29,45,53,57], for enabling throw-or swing gestures to transfer media between devices [14,42], and for uni-stroke letter [1] or symbol [30,63] recognition in combination with acceleration data.…”
Section: Interacting With the Smartphonementioning
confidence: 99%
“…Many studies have shown that using the phone's movements, combined with touch, can outperform the use of many other options (i.e. touch-only devices, mouse, Wii remotes, 6DoF wand) in 3D object translation/rotation tasks [28,29,44,56]. However, this requires users to calibrate their smartphone's IMU to determine its correct orientation [15,16,50] each time they intend to use it.…”
Section: Interacting With the Smartphonementioning
confidence: 99%